Relationship Between Patient Demographics and Biologic Therapy Use in Inflammatory Bowel Disease. A Single Center Cross‐Sectional Study - Mohammad Shehab; Abdulwahab Alsayegh; Munirah Alabdulhadi; Shahed Snober; Nouf Aleissa; Ahmad Alfadhli (JGH Open)
ABSTRACT Introduction Biologic therapies treat patients with moderate to severe inflammatory bowel disease (IBD). This study aims to investigate the demographics of biologic therapy use and its association with patient characteristics, a topic that has not yet been thoroughly assessed in our region. Methods Electronic health record data from June 1, 2021, to May 31, 2023, were collected at a tertiary care IBD center in Kuwait. The primary outcome of this single‐center cross‐sectional study was to assess the demographics of use of various biologic therapies among patients with IBD. The secondary outcome was to assess whether the type of biologic therapy differed based on gender, age, and IBD type. Results Among the 513 patients using biologic therapy in this study, there were 210 (40.9%) on adalimumab (ADL), 154 (30.0%) on infliximab (IFX), 112 (21.9%) on ustekinumab (UST), and 33 (6.4%) on vedolizumab (VDZ). Patients taking VDZ were more likely to have ulcerative colitis (UC) (p < 0.001) and were more likely to be over 30 years old (p < 0.001). In contrast, patients on UST were less likely to be over 30 (p = 0.011) and more likely to have Crohn's disease (CD) (p < 0.001). In addition, patients on ADL were more likely to have Crohn's disease (p = 0.003), as were patients on IFX (p < 0.001). Conclusion Patients taking VDZ were more likely to have UC and be over 30 years of age, while those on UST were more likely to be under 30 years of age and to have CD. Additionally, patients on ADL and IFX were more likely to have CD. This study highlighted the need for further research evaluating physicians' preferences and the effectiveness of different biological therapies in patients with IBD.